Penerapan Terapi Puzzle Untuk Meningkatkan Fungsi Kognitif Pada Lansia di Panti Werdha Palembang - Deesirene Rohani Simanullang; Lilik Pranata; Aprida Manurung (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
An elderly person is someone who reaches the age of > 60 years. This increase in age will result in a decrease in the ability of the body's functions, one of which is the nervous system, namely a mild, moderate decline in cognitive function and even dementia. Severe dementia will result in elderly people being unable to carry out activities so that they will experience elderly people who are not prosperous and happy. To overcome this, puzzle therapy is needed. Puzzle therapy is a game of arranging certain shapes until they become a complete image or form a certain pattern. This is to stimulate and improve the cognitive function of the brain. It is known that nursing care for elderly people with decreased cognitive function is provided by providing puzzle therapy. This case study uses a descriptive method with a nursing process approach carried out on 3 clients using a One Group Pretest Posttest puzzle therapy research design on cognitive function in the elderly. The implementation results showed that there was a change in the MMSE score after being given puzzle therapy for 5 consecutive days, namely Mrs. F from 21 to 23, Mrs. L from 22 to 24 while Mrs. E of 16 and still has a score of 16. The average MMSE score which increased after being given puzzle therapy was 2 scores. It is hoped that the results of this case study can become an application for implementing puzzle therapy to improve cognitive function in the elderly where caregivers or nursing home staff can also make puzzle therapy a routine activity that can be carried out every week at the Dharma Bhakti KM 7 Palembang Nursing Home.